Early postnatal exposure to bicuculline modulates E/I balance and induces ASD-like behavioral phenotypes in mice - Dongpil Shin; Eunbi Cho; Kwanghoon Park; ChiHye Chung; Dong Hyun Kim; Se Jin Jeon; Chan Young Shin (Animal Cells and Systems)
Autism spectrum disorder (ASD) is a neurodevelopmental condition characterized by social interaction deficits and repetitive behaviors. While precise causes of ASD remain elusive, growing evidence highlights that an imbalance in excitatory and inhibitory (E/I) signaling is a pivotal factor in ASD development and modulation. Balanced E/I neurotransmission is critical for circuit formation, synaptic plasticity, and developmental timing. However, key questions persist, including the critical perturbation window, neurological and neurodevelopmental effects, and clinical implications of E/I imbalance. This study investigated early-life modulation of the GABAergic system’s impact on E/I balance and ASD-like behaviors in mice. Mice were treated with bicuculline, a GABAA receptor antagonist, from postnatal days 7–11, and behavioral tests were conducted during adolescence. Results revealed deficits in social interaction in both male and female mice and increased repetitive behaviors in bicuculline-treated male mice. Electrophysiological recordings in the mPFC indicated reduced resting membrane potential, heightened neuronal excitability, and a shift in the E/I ratio. In the hippocampus, recordings displayed enhanced LTP and altered synaptic plasticity. DEG analysis of the PFC in bicuculline-treated mice unveiled aberrant gene profiles related to the regulation of synaptic function. Clinical significance and underlying mechanisms of abnormal brain activity, neurodevelopment, and ASD-related behaviors prompted by neonatal bicuculline treatment require further investigation. Nevertheless, these results suggest that GABAergic signaling disruption during the neonatal period might contribute to ASD-related brain pathophysiological changes.